Sedentary time, metabolic abnormalities, and all-cause mortality after myocardial infarction: A mediation analysis. (January 2019) - Wu, Zhijun; Huang, Zhe; Wu, Yuntao; Huang, Shue; Wang, Yanxiu; Zhao, Haiyan; Chen, Shuohua; Wu, Shouling; Gao, Xiang
Background: Sedentary time was associated with myocardial infarction (MI) and metabolic diseases in previous studies. Purpose: To investigate whether sedentary time measured before disease onset was associated with all-cause mortality among MI survivors and whether the sedentary time–mortality association was mediated by physical activity status and metabolic phenotypes. Methods: In this prospective community-based cohort including 101, 510 Chinese adults, we used sedentary time, evaluated at 2006 (baseline), to predict further all-cause mortality among individuals who then developed new onset MI from 2006 to December 2013 ( n  = 989). The post-MI mortality was ascertained after the first non-fatal MI until December 2014. We assessed the mediating effects of physical inactivity and metabolic factors on the sedentary time-mortality association. Results: During 7 years follow up, 180 deaths occurred among these participants with incident MI. Prolonged sedentary time was associated with a higher risk of mortality among MI survivors. The adjusted hazard ratio (HR) of mortality for sedentary time 4–8 hours/day versus <4 hours/day, was 1.62 (95% confidence interval (CI) 1.14–2.31). A high amount of sedentary time (>4 hours/day) and inactive physical activity had an increased risk of all-cause mortality (HR: 2.74, 95% CI 1.34–5.60), relative to those with sedentary time ≤4 hours/day and moderate/vigorous physical activity. Physical inactivity and metabolic factors mediated a small proportion (≤9.2 % for all) of the total association between sedentary time and post-MI mortality. Conclusion: High sedentary time was significantly associated with all-cause mortality among MI survivors, independent of physical activity status and metabolic abnormalities.